ANIMISME DAN MAGIS PADA MASYARAKAT MODERN: STUDI SOSIAL-KEAGAMAAN MASYARAKAT PESISIR TAPANULI TENGAH - Muhamad Burhanuddin; Hutabarat, Azdisyah; Tanjung, Sri Rahayuni; Siti Ramadhani (Academic Journal of Islamic Principles and Philosophy, 2023)
Modern society is a society that has a very well-established and rational mindset in doing something. However, in reality on the ground there are still practices of animism and magic in faith and healing in the Central Tapanuli Society. Initially in E. B. Taylor's theory, human beliefs originated from animism, in religions of a local or large nature undergoing a religious evolution with complexity in the practice of worship. In his theory, J.G. Frazer revealed that magic is a human attempt to control the forces of nature. The method in this research uses text literature on the beliefs of the people of North Sumatera and the oral study of the history of the community of Central Tapanuli. This research confirms that there are still practices of animism and magic in the life of Central Tapanuli coastal communities.